THE EFFECT OF FEEDING LEVEL ON THE GENETIC RESISTANCE OF LOCAL BREEDS INFECTED WITH HAEMONCHUS CONTORTUS - Ali, D A; AL-Zuhairy, M; Affat , A M (The Iraqi Journal of Veterinary Medicine, 1996)
Sixty sheep of three local breeds (Awassi, Hamdani, Karadi) of age, 6-8 months were divided to two groups, the first fed on low level of nutrition. Each group then divided into Two subgroups, the first was infected with 500 larvae / Kg Haemonchus contortus & the second was used as a control. Egg G. fecal sample, staple length, P. c. v. Hb; weight gain were recorded weekly for 13 week post infection. Results revealed that all sheep traits of low level nutrition were significantly (P<0.01) more affected than high level nutrition group. Awassi breed was more reistant to infection with H. contortus than Hamdani & Karadi breeds.